2016
DOI: 10.1111/jgh.13195
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pre‐ and post‐resectional histologic discrepancies in gastric low‐grade dysplasia: A comparison of white‐light and magnifying endoscopy

Abstract: MENBI can provide more accurate information than white-light endoscopy for the prediction of pre- and post-resectional histologic discrepancies in biopsy-proven gastric LGD. Endoscopic resection is strongly recommended in cases with surface erythema on conventional white-light endoscopy or positive MENBI, irrespective of the lesion size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
4
14
1
Order By: Relevance
“…have shown that erythema and positive ME‐NBI findings are independent factors for a histological upgrade of LGD. In this study we found that a lesion of >20 mm in diameter, surface redness and positive ME‐NBI results were risk factors for histological upgrade, and positive ME‐NBI results had the highest odds ratio among the risk factors, which is consistent with the results of Hwang et al …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…have shown that erythema and positive ME‐NBI findings are independent factors for a histological upgrade of LGD. In this study we found that a lesion of >20 mm in diameter, surface redness and positive ME‐NBI results were risk factors for histological upgrade, and positive ME‐NBI results had the highest odds ratio among the risk factors, which is consistent with the results of Hwang et al …”
Section: Discussionsupporting
confidence: 92%
“…The abovementioned data show that the risk of biopsy‐diagnosed LGD lesions to progress to invasive cancers is low, and most LGD lesions regress to gastritis or show no histological change. However, accumulated evidence has shown that the rates of progression from biopsy‐diagnosed LGD to HGD or gastric adenocarcinoma after endoscopic resection are higher, ranging from 12.1% to 63% . In our study, the upgrade rates of LGD to HGD or adenocarcinoma were as high as 48.9%, indicating the need for the aggressive management of biopsy‐diagnosed LGD.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations